Benefit finding in adults living with somatic non-communicable chronic disease: a systematic review on the mean level and the prevalence - Liu, Zhunzhun; Hu, Xiang; Arndt, Volker; Thong, Melissa S. Y. (Frontiers in Psychiatry, 2026)
IntroductionBenefit finding (BF) refers to the phenomenon of identifying positive changes from challenging circumstances. This review aimed to comprehensively assess the BF prevalence in persons with somatic non-communicable chronic diseases (pSNCDs).Materials and methodsElectronic databases were systematically searched using the concept “benefit finding”. Eligible studies (adult persons with SNCDs, BF measured by the Benefit Finding Scale, written in English, observational in design, and published until June 30, 2023) were reviewed and underwent quality and publication bias assessments; prevalence and mean were extracted and synthesized.ResultsOf the 55 included articles, 35 were rated “weak”, 18 “moderate”, and 2 “strong” in quality. BF mean was 3.25 (25,972 observations), BF prevalence was 97.5% (10,720 observations), and moderate-to-high BF prevalence was 74.1% (12,363 observations). Subgroup analysis indicated higher moderate-to-high BF in cancer survivors (highest: 89% in breast cancer) than non-cancer survivors (highest: 72.4% in HIV). The lowest BF and moderate-to-high BF prevalence occurred in cancer survivors aged 60 +. Meta-regression suggested that study design and quality, time since diagnosis, gender, and mean age may explain heterogeneity in BF means. Subgroup analyses showed the lowest BF mean in pSNCDs aged 70+ years.DiscussionPersons with SNCDs generally reported a moderate BF mean. Age is an important factor associated with BF. Future studies are needed to better understand how pSNCDs find/perceive benefits, especially for older adults aged 60+ years.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022308513, identifier CRD42022308513.